METTL3-mediated m6A modification of ATG7 regulates autophagy-GATA4 axis to promote cellular senescence and osteoarthritis progression. Issue 1 (27th October 2021) - Chen, Xiang; Gong, Wang; Shao, Xiaoyan; Shi, Tianshu; Zhang, Lei; Dong, Jian; Shi, Yong; Shen, Siyu; Qin, Jianghui; Jiang, Qing; Guo, Baosheng
Abstract : Objective: The aim of the study was to investigate the role and regulatory mechanisms of fibroblast-like synoviocytes (FLSs) and their senescence in the progression of osteoarthritis (OA). Methods: Synovial tissues from normal patients and patients with OA were collected. Synovium FLS senescence was analysed by immunofluorescence and western blotting. The role of methyltransferase-like 3 (METTL3) in autophagy regulation was explored using N6-methyladenosine (m 6 A)-methylated RNA and RNA immunoprecipitation assays. Mice subjected to destabilisation of the medial meniscus (DMM) surgery were intra-articularly injected with or without pAAV9 loaded with small interfering RNA (siRNA) targeting METTL3. Histological analysis was performed to determine cartilage damage. Results: Senescent FLSs were markedly increased with the progression of OA in patients and mouse models. We determined that impaired autophagy occurred in OA-FLS, resulting in the upregulation of senescence-associated secretory phenotype (SASP). Re-establishment of autophagy reversed the senescent phenotype by suppressing GATA4. Further, we observed for the first time that excessive m 6 A modification negatively regulated autophagy in OA-FLS. Mechanistically, METTL3-mediated m 6 A modification decreased the expression of autophagy-related 7, an E-1 enzyme crucial for the formation of autophagosomes, by attenuating its RNA stability. Silencing METTL3 enhanced autophagic flux and inhibited SASP expression in OA-FLS. Intra-articular injection of synovium-targeted METTL3 siRNA suppressed cellular senescence propagation in joints and ameliorated DMM-induced cartilage destruction. Conclusions: Our study revealed the important role of FLS senescence in OA progression. Targeted METTL3 inhibition could alleviate the senescence of FLS and limit OA development in experimental animal models, providing a potential strategy for OA therapy.